2005
DOI: 10.1111/j.1365-2222.2005.02184.x
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal lipopolysaccharide‐exposure prevents allergic sensitization and airway inflammation, but not airway responsiveness in a murine model of experimental asthma

Abstract: This study provides first experimental evidence that LPS may already operate in prenatal life in order to modulate the development of allergies in the offspring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
110
1
7

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(123 citation statements)
references
References 35 publications
5
110
1
7
Order By: Relevance
“…Similarly, we showed that exposure of the mother to farm animals during pregnancy was strongly associated with a subsequent reduced prevalence of hayfever, asthma and eczema [20]. The importance of prenatal exposures has also been confirmed in animal models of asthma [70]. In addition, several studies have shown inverse associations between endotoxin exposure in the first year of life and asthma symptoms later in childhood [52].…”
Section: A U-shaped Response?mentioning
confidence: 58%
“…Similarly, we showed that exposure of the mother to farm animals during pregnancy was strongly associated with a subsequent reduced prevalence of hayfever, asthma and eczema [20]. The importance of prenatal exposures has also been confirmed in animal models of asthma [70]. In addition, several studies have shown inverse associations between endotoxin exposure in the first year of life and asthma symptoms later in childhood [52].…”
Section: A U-shaped Response?mentioning
confidence: 58%
“…Some studies have focused on the anti-inflammatory effects of omega-3 fatty acids on asthma (Blümer et al, 2005). Wallace et al (2001) reported that omega-3 fatty acids are effective on T-helper 1 cells and eicosanoid metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Of importance is the maternal environment, suggesting that maternal immunity may be transferred or at least influence the offspring. In experimental murine models, the mother is treated with lipopolysaccharide which attenuated allergic disease and associated inflammation in offspring [22][23][24]. One study explored the effect of LPS on female BALB/c mice before conception and during pregnancy.…”
Section: Animal Models Show the Benefit Of Microbial Exposure During mentioning
confidence: 99%